PENGGANTIAN APARATUR SIPIL NEGARA (ASN) DENGAN ROBOTIK DALAM MEWUJUDKAN DIGITALISASI BIROKRASI DI ERA REVOLUSI INDUSTRI 4.0 - Yusep Mulyana Yusep Mulyana (JISOS: JURNAL ILMU SOSIAL, 2022)
The replacement of ASN with robotics has actually been seen with various digital transformations carried out by the government. The current government continues to carry out digital transformation in the services provided by the management of the state civil apparatus. This has been going on for several years. The use of technology is seen as achieving bureaucratic effectiveness and budget savings, because with so many positions being replaced by technology, the state certainly does not need to pay salaries for civil servants. To accelerate the process of developing the Indonesian bureaucracy SuperApp, it is necessary to immediately build a National Data Center as a home for One Data Indonesia, build shared information and communication technology (ICT) infrastructure, prepare machine learning and artificial intelligence (AI) technology that will be used to bigdata analytics as the basis for various decision-making and policy development needs. With the Indonesian bureaucracy's SuperApps, various public services can be done online.